The Castle Corona - Creech, Sharon; Diaz, David (New York Joanna Cotler Books, 2007)
Two orphaned peasant children discover a mysterious pouch, the contents of which lead them to the majestic Castle Corona, where their lives may be transformed forever.
Long ago and far away ... -- A discovery -- It only ... -- The meek, the spare, the spoiled -- The peasants -- The king and queen -- An encounter -- The royal riders -- The hermitage -- The pouch -- The hermit -- Wisdom -- The old woman -- Preparations -- The count and countess -- The dirty beetles -- Royal duties -- The wordsmith -- The burden -- A gift -- One story ends -- The cornos -- The inventories -- Castle dreams -- The intrusion -- Resolve -- Castle conversations -- Cottage conversations -- Greener grass -- Free? -- Kidnapped -- In a towering castle ... -- The new hermit -- The tasters -- Duty calls -- Bother, bother, bother -- A dream? -- Peasant ignorance -- New inventories -- A duel -- The heir and a hair -- The queen and a bean -- The peasant and a pheasant -- A story was told ... -- A new story -- The castle's tale -- Restless -- The mission -- A favor -- An unexpected reception -- Interrupted -- Hermit in the tunnel -- Poison -- Beans -- The summons -- A noble prince, a peasant girl -- The hermit and the orphans -- A tale ends -- Ever after.
Keywords: Orphans -- Juvenile fiction; Siblings -- Juvenile fiction; Kings and rulers -- Juvenile fiction; Orphans -- Fiction; Siblings -- Fiction; Italy -- Juvenile fiction; Italy -- Fiction